The Strength Of Composite Polyamide With Different Molding Orientation Under High Strain Tension Load - Jeganathan, Arvind Dayvaa (Universiti Sains Malaysia, 2020)
This project investigates a functionally graded material characteristic strength as a result of different fibre flow orientations during the moulding process. The experiment is conducted using a SHPB machine which was designed and developed in the School of Mechanical Engineering USM. The functionally graded material used in this work is a composite polyamide known as Grivory. To characterize the distribution of the fillers in the material, a scanning electron microscope were employed. Scanning electron microscopy is used to examine the filler region, and a Universal Testing Machine is used to evaluate the specimen's tensile strength. In this work, SHPB is used to determine the specimen's dynamic mechanical properties at high strain rate. In addition, a data collecting system for data processing and analysis has been developed to characterize the behaviour of the tested composite polyamide. It was determined that striker velocity to achieve strain rate of 800s-1 is at 10.1393 m/s. The compressed pressurised tank is modified to bigger diameter from original 0.0508m to 0.1016m so that to increase the air volume to give higher speed to the bars in the impact test. Based on experimental value, the striker velocity provided by the air compressor at 9 Bar is 10.25 m/s. As the pressure tank is modified, it can now increase the volume of air into the gun barrel and hence increase the air force to the striker which in return increase the speed of incident bar after the striker strike the anvil on the incident bar. This means that the material is underwent strain rate of 800s-1. Lastly, from the UTM test, the maximum tensile stress for specimen P is 107.03 MPa with load at maximum of 642.2 N and maximum tensile stress for specimen C is 64.2 MPa with load at maximum of 385.3 N. At the pressure of 9 bar, the high strain rate tensile testing achieve by the Specimen P is 836.79 s-1, at the high peak of maximum stress at 41.25 MPa; for specimen C, the high strain rate tensile testing is 803.555 s-1, at the high peak of maximum stress at 40.37 MPa. Based on the stress strain curve obtain using SHPB test, we can conclude that the specimen P give higher strain rate compare to Specimen C.